Total Fat Content and Fatty Acid Profile of Fine-Aroma Cocoa From Northeastern Peru - Oliva-Cruz, Manuel; Mori-Culqui, Pati Llanina; Caetano, Aline C.; Goñas, Malluri; Vilca-Valqui, Nuri C.; Chavez, Segundo G. (Frontiers in Nutrition, 2021)
Cocoa beans are the raw material for the chocolate industry. In this study, the total fat contents and fatty acid profiles of fine-aroma cocoa beans of 30 cocoa ecotypes from northeastern Peru were evaluated. Results showed that SJJ-1 and ACJ-11 ecotypes from San Martin and Amazonas regions, respectively, presented highest percentages of total fat with an average of 30.49%. With respect to fatty acid profiles, it was found that cocoa ecotypes are composed of 10 fatty acids (C14:0, C16:0, C16:1, C18:0, C17:0, C18:1, C18:2, C18:3, C20:0 and C22:0); based on this profile, 5 clusters were determined. Cluster 5 had the highest content of C17:0 fatty acid (0.47%); however, the clusters 1 , 2 ,3 and 4 had the lowest content of this fatty acid (0.37%, 0.32%, 0.32% respectively). The clusters 3 and 4 showed the highest content of C16:0 fatty acid (31.13% y 28.97% respectively). The clusters 3 and 5 contained the highest content of the acid C18:1 (27.08% y 26.82% rspectively). The PCA found that C18:0 and C20:0 fatty acids are correlated, and are fundamentally opposite to C18:1, C16:0 and C18:3 acids. These results may be useful in identifying raw material for the development of specialty chocolates with better nutritional value than traditional cocoa.